Bravo football club - Gorman, Sean; Lusher, D.; Reeves, K. (Routledge, 2016)
The Bravo football club is an AFL club that participated in this Australian Research Council project Assessing the Australian Football League’s Racial and Religious Vilification Laws to promote community harmony, multiculturalism and reconciliation. Bravo participated in both the surveys and the interviews. This club and its players and staff have all been deidentified as required by Curtin University’s ethics guidelines.